How our Bible came to us: The story of the book that changed the world - Meryl Doney 1942-; Peter Dennis 1950- (England USA Lion Publishing, 1985)
Discusses how the Bible came into being, who wrote it, early and modern translations, monks and manuscripts, and the importance of the Bible.
Cover has subtitle: the story of the book that changed the world.
"A Lion book."
Includes index.
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible